PENGARUH UANG SAKU, PENGENDALIAN DIRI DAN IKLAN TERHADAP PERILAKU KONSUMTIF MAHASISWA JURUSAN EKONOMI ISLAM FAKULTAS EKONOMI DAN BISNIS ISLAM UIN SUMATERA UTARA - Anggi Adistika Harahap; Sugianto Sugianto; Juliana Nasution (Jurnal Ekonomi Bisnis dan Kewirausahaan, 2024)
Students spend a lot of time with their peers, so that students experience changes in their lifestyle and appearance. These changes often occur when they see new and interesting things, especially their consumer behavior. The study aims to answer the following questions: 1) Does pocket money affect the consumer behavior of students majoring in Islamic Economics, Faculty of Islamic Economics and Business, UIN North Sumatra, class of 2017, 2) Does self-control affect the consumer behavior of students majoring in Islamic Economics, Faculty of Islamic Economics and Business, UIN North Sumatra, class of 2017, 3) Does advertising affect the consumer behavior of students majoring in Islamic Economics, Faculty of Islamic Economics and Business, UIN North Sumatra, class of 2017, 4) Do pocket money, self-control and advertising affect the consumer behavior of students majoring in Islamic Economics, Faculty of Islamic Economics and Business, UIN North Sumatra, class of 2017? This study uses a quantitative approach with a total of 73 people based on Proportional Random Sampling, data was collected using a questionnaire technique. The analysis used in this study is multiple linear regression analysis. The results of the study indicate that partially the variables of pocket money (X1), self-control (X2), advertising (X3), and have a significant effect on the consumer behavior of students majoring in Islamic Economics, Faculty of Islamic Economics and Business, UINSU because the significant value is <0.05. This is obtained by the significant value of pocket money 0.021, self-control 0.008 and advertising 0.000. The effect of the pocket money variable partially on the consumer behavior of students is 20.4%, the self-control variable is 26.6% and advertising is 51.4%. Simultaneously, the variables of pocket money (X1), self-control (X2) and advertising (X3) have a significant effect on the consumer behavior of students majoring in Islamic Economics, Faculty of Islamic Economics and Business with a significant value of 0.000 <0.05 and its influence is 48.9%.